Субетнічна ідентичність як фактор формування регіональної політики в сучасній Литві - Кальнюс, П. (Народна творчість та етнологія, 2011)
The article analyzes attempts to review the existing concept of the Lithuanian nation in the present-day Lithuania and to prove that Lithuanian nation consists of two or more ethnic communities. Such a comprehension resulted in the proposals to change the administrativeterritorial division of Lithuania and review of the distribution of power and competence between the center and the ethnic regions. Keywords: region, traditional culture, dialect, ethnicity, Lithuania, Samogitia.